2007
DOI: 10.1111/j.1475-097x.2007.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the peripheral circulation in COPD patients

Abstract: In COPD patients, significant alterations in the peripheral circulation were observed. Moreover, the magnitude of changes in the peripheral circulation was related to the severity of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
3
1
3
Order By: Relevance
“…18e22 Noninvasive techniques measuring arterial stiffness and vascular resistance of large and small vessels are increasingly used as surrogate markers for early atherosclerosis and the risk of cardiovascular events. 19,23,24 Previous studies 25,26 have shown that mean aortic pulse wave velocity as well as inflammatory markers and augmentation index, were significantly greater in COPD patients compared to healthy control subjects. The authors concluded that the increased arterial stiffness is related to the severity of the airflow obstruction in COPD.…”
Section: Introductionmentioning
confidence: 98%
“…18e22 Noninvasive techniques measuring arterial stiffness and vascular resistance of large and small vessels are increasingly used as surrogate markers for early atherosclerosis and the risk of cardiovascular events. 19,23,24 Previous studies 25,26 have shown that mean aortic pulse wave velocity as well as inflammatory markers and augmentation index, were significantly greater in COPD patients compared to healthy control subjects. The authors concluded that the increased arterial stiffness is related to the severity of the airflow obstruction in COPD.…”
Section: Introductionmentioning
confidence: 98%
“…А.Boussuges et al также обнаружили увеличение артерильной ригидности у пациентов с ХОБЛ [12]. Авторы не исключали, что причиной повышения ар териальной ригидности могли быть воздействие си гаретного дыма, гипоксия, системное воспаление, гиперактивность симпатической нервной системы.…”
Section: Discussionunclassified
“…Возможно, именно развитие артериальной ри гидности и эндотелиальной дисфункции является связующим звеном между ХОБЛ и сердечно сосу дистыми заболеваниями (ССЗ). Относительно не давно выполнены исследования, посвященные изу чению механических свойств артерий у больных с респираторной патологией [11][12][13]. Однако кли нико патогенетические и функциональные аспекты этих нарушений неоднозначны и изучены недоста точно.…”
Section: резюмеunclassified
“…Cardiovascular disease is one of the most prevalent comorbidities in COPD [11][12][13][14] . COPD is associated with a 2-3-fold increase in the risk of ischemic heart disease, stroke, and sudden death [ 14 ] .…”
Section: Common Medical Comorbidities Of Copdmentioning
confidence: 99%